Effects of carteorol on cerebral blood flow in stroke patients - Watanabe, Shigeru; Kobari, Masahiro; Obara, Katsuyuki; Fukuuchi, Yasuo; Nogawa, Shigeru (Japanese Journal of Stroke, 1995)
The acute effects of β-blocker include a decrease in cerebral blood flow (CBF). However, few reports have been published on the acute effects of newly developed β-blockers on CBF. We examined the effects of carteorol on CBF in 10 stroke patients with hypertension during the subacute phase. The subjects consisted of 7 patients with cerebral infarction and 3 patients with cerbral hemorrhage with an average age of 58.2 years. CBF was measured before and at 30 min after oral administration of 10 mg carteorol by the stable xenon CT-CBF method. We analyzed the effects on arterial blood pressure and CBF in 9 patients whose plasma levels of carteorol were detectable. At 30 min after carteorol administration, the mean arterial blood pressure was significantly reduced from 126.1 ± 8.1 mmHg to 120.4 ± 8.5 mmHg (p<0.05). The mean CBF values before and after carteorol administration were 37.8 ± 4.3 ml/100 g brain/min and 40.2± 3.2 ml/100 g brain/min, respectively. The degrees of increase in CBF in both the diseased and healthy hemispheres were not significantly different. The changes in CBF were significantly correlated with the basal mean arterial blood pressure (r = 0.72, p <0.05). These findings indicate that carteorol can act as potent antihypertensive agent without deterioration of the cerebral circulation.